Vibrational Spectroscopy Characterization and Anticoagulant Activity of a Sulfated Polysaccharide from Sea Cucumber Athyonidium Chilensis - Matsuhiro-Yamamoto, B; Matsuhiro-Yamamoto, B; Torres-De la Fuente, R (2012)
Extraction of Athyonidium chilensis body wall afforded a light brown powder in 4.2% yield which was fractionated by ion-exchange chromatography. The main fraction F1 contained glucuronic acid, galactosamine and fucose in a molar ratio of 1.0:1.1:1.1, and 32.9% of sulfate group. The second derivative FT-IR spectroscopy and Surface-enhanced Raman scattering (SERS) give more information than the normal IR and Raman spectroscopies. The broad band in the normal FT-IR spectrum of F1 at 850.6 cm -1 assigned to sulfate group was resolved in the second derivative spectrum into three bands at 856.4 cm -1, 837.4 cm -1 and 818.6 cm -1 assigned to sulfate group attached to axial C4 and equatorial C2 and C6, respectively, in glycosidic residues. The most important bands in SERS of F1, but not observed in Raman spectrum are bands at 1648 cm -1 (?CO), 1377 cm -1 (?C-H) assigned to methyl group of N-acetyl group, at 1173 cm -1 and at 956.2 cm -1 (?C-O-C) of glycosidic linkage; and bands at 925.5 cm -1 and 890.4 cm -1 (?C 1-H) assigned to ? and ? anomeric configurations of glycosidic residues, respectively. By NMR studies, glycosidic linkages and sulfation pattern of F1 was confirmed. Results obtained indicated that fraction F1 is chondroitin 4,6-disulfate substituted at position O-3 of glucuronic acid by partially 2,4-disulfated ?-fucopyranosyl residues. Moreover, the anticogulant activity, measure in APTT of F1 showed at low concentration, a good correlation with heparin. © 2012 Elsevier Ltd. All rights reserved.